Modulation of β-Amyloid Fibril Formation in Alzheimer’s Disease by Microglia and Infection - Brown, Madeleine R.; Radford, Sheena E.; Hewitt, Eric W. (Frontiers in Molecular Neuroscience, 2020)
Amyloid plaques are a pathological hallmark of Alzheimer’s disease. The major component of these plaques are highly ordered amyloid fibrils formed by amyloid-β (Aβ) peptides. However, whilst Aβ amyloid fibril assembly has been subjected to detailed and extensive analysis in vitro, these studies may not reproduce how Aβ fibrils assemble in the brain. This is because the brain represents a highly complex and dynamic environment, and in Alzheimer’s disease multiple cofactors may affect the assembly of Aβ fibrils. Moreover, in vivo amyloid plaque formation will reflect the balance between the assembly of Aβ fibrils and their degradation. This review explores the roles of microglia as cofactors in Aβ aggregation and in the clearance of amyloid deposits. In addition, we discuss how infection may be an additional cofactor in Aβ fibril assembly by virtue of the antimicrobial properties of Aβ peptides. Crucially, by understanding the roles of microglia and infection in Aβ amyloid fibril assembly it may be possible to identify new therapeutic targets for Alzheimer’s disease.